ANALISIS STRATEGI PROMOSI DI TOKO KUE PLASINDO CAKE & BAKERY DALAM MEMPERKUAT CITRA DAN KEPUASAN KONSUMEN - Mariam, Siti (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2024)
This research discusses marketing strategy as the key to the success and growth of a company. Marketing is the main element in meeting consumer needs and achieving business goals through a marketing mix which includes product, price, place and promotion. This research is a qualitative descriptive study that explores the use of the marketing mix in the context of increasing consumer satisfaction. The main focus of research is on marketing strategies that include product innovation, competitive prices, strategic locations, effective advertising campaigns, and their impact on customer satisfaction. In the short term, research shows the importance of winning over consumers with new products, while in the long term, maintaining product quality is key to retaining the existing consumer base. An effective marketing strategy also includes developing and implementing multi-purpose markets as well as sustainable market segmentation to better meet and serve consumer needs. In conclusion, this research provides insight into how marketing strategies can be used to increase competitiveness and consumer satisfaction, as well as maintain a company's position in a competitive market